Slavery, race and conquest in the tropics Lincoln, Douglas, and the future of Latin America - May, Robert E. 1943- (Cambridge Univ. Press, 2013)
"Slavery, Race, and Conquest in the Tropics challenges the way historians interpret the causes of the American Civil War. Using Abraham Lincoln and Stephen Douglas's famed rivalry as a prism, Robert E. May shows that when Lincoln and fellow Republicans opposed slavery in the West, they did so partly from evidence that slaveholders, with Douglas's assistance, planned to follow up successes in Kansas by bringing Cuba, Mexico, and Central America into the Union as slave states. A skeptic about "Manifest Destiny," Lincoln opposed the war with Mexico, condemned Americans invading Latin America, and warned that Douglas's "popular sovereignty" doctrine would unleash U.S. slaveholders throughout Latin America. This book internationalizes America's showdown over slavery, shedding new light on the Lincoln-Douglas rivalry and Lincoln's Civil War scheme to resettle freed slaves in the tropics"..